Correlation, crossover and broken scaling in the Abelian Manna model - Chen,L; Pruessner,G; Hoai,NH (Physical Review Research, 2024)
The role of correlations in self-organized critical (SOC) phenomena is investigated by studying the AbelianManna model (AMM) in two dimensions. Local correlations of the debris left behind after avalanches aredestroyed by rearranging particles on the lattice between avalanches, without changing the one-point particledensity. It is found that the spatial correlations are not relevant to small avalanches, while changing the scalingof the large (system-wide) ones, yielding a crossover in the model’s scaling behavior. This crossover breaks thesimple scaling observed in normal SOC.